Travel-associated illness in children in pre-pandemic Western Sydney, 2018-2020 - Paula Mazzocato; Karin Leder; Lucy Deng; Philip Britton (Sax Institute, 2024)
Objectives and importance of study: Australian children frequently travel overseas, but little is known about their travel-related morbidity. We aimed to describe the spectrum of illness and injury in returned travellers presenting to the largest paediatric referral centre in NSW, the Children's Hospital at Westmead (CHW). Study type: Observational cohort study. Methods: In the 18 months immediately before the COVID-19 pandemic (2018-2020), we prospectively collected demographic, travel and clinical data from children with travel-acquired illness or injury identified by active surveillance of CHW Emergency Department attendees and referrals to the infectious diseases service. Results: We identified 587 returned child travellers with an illness or injury associated with overseas travel. Most were aged younger than 5 (62.8%) and had travelled within the Asia-Pacific region (84.6%). The main reason for travel, where recorded (50.3%), was visiting friends and relatives (VFR)(65.4%). Most travellers (90.1%) had a common childhood infection, illness or injury coincidentally acquired during travel, including respiratory infection (37.5%), acute diarrhoea (15.7%) and nonspecific febrile illness (13.1%). Exotic/nonendemic infections were uncommon (9.9%, including potential rabies exposure) but were associated with much higher admission rates than 'cosmopolitan' (globally distributed) diseases (74.2% vs 21.9%). Most of these occurred in VFR travellers (86.3%); enteric fever, largely acquired in South Asia, predominated (51.7%). One in five admitted patients had a disease for which specific pretravel vaccination is available. Receipt of pretravel vaccines was infrequently recorded. Conclusions: Returned child travellers in Western Sydney frequently presented with respiratory infections and may be a key population for surveillance of imported respiratory viruses. The burden of exotic disease was small and borne by VFR travellers. Travel-related illness in Western Sydney could be reduced by health education of travellers and targeted pretravel vaccination, especially typhoid vaccination for VFR travellers to South Asia. Universal, systematic screening of emergency department attendees for recent overseas travel would improve surveillance of travel-related illness.